Influence of selective acid etching on microtensile bond strength of a self-adhesive resin cement to enamel and dentin - Lúcia Trazzi Prieto; Cíntia Tereza Pimenta Araújo; Maria Malerba Colombi Humel; Eduardo José Souza-Junior; Carlos Tadeu dos Santos Dias (Universidade Estadual de Campinas, 2015)
Aim: To evaluate the selective acid etching of enamel and dentin on microtensile bond strength (µTBS) of a self-adhesive resin cement. Methods: Forty-eight bovine teeth were selected and had the buccal surface ground to obtain a flat dentin (n=24) or enamel (n=24) surface. Z250 composite resin blocks (4 x 3 x 8 mm) were prepared for cementation at enamel and dentin. Each substrate received three experimental resin cementation strategies: 1) 37% phosphoric acid etching before the application of RelyX Unicem; 2) application of RelyX Unicem alone; 3) RelyX ARC as a control. Samples were light-cured using a halogen light (Optilux 501, 700mW/cm2 ), for 40 s. Hourglass-shaped specimens were obtained and submitted to a tensile strength at a crosshead speed of 0.5 mm/min in a universal testing machine. For statistical analysis, data were submitted to ANOVA and Tukey's test at a pre-set alpha (á=0.05). Results: RelyX Unicem showed similar bond strength value (16.5 MPa) when compared to the pretreatment with acid etching (11.9 Mpa) and to the conventional resin cement (18.1 MPa) for enamel. All luting strategies presented similar dentin bond strength, but significantly lower than enamel bond strength. Conclusions: Acid etching prior to RelyX Unicem application did not improve microtensile bond strength for enamel and dentin.